الشائعات وأثرها في تهديد الأوطان وطرق معالجتها: دراسة في ضوء الهدي النبوي - المورعي، أحمد بن نافع بن سليمان (جامعة الأزهر - كلية أصول الدين والدعوة بالزقازيق, 2021)
إن تداول الشائعات وانتشارها من أخطر مهددات الأمن الوطني السياسية، والاقتصادية، والاجتماعية، وخاصة ما يكون في الأمور الهامة، والأحداث الجسيمة كأمور الحرب، والعلاقات الدولية، تلك التي ما إن انتشرت في مجتمع ما حتى تحول أمنه قلقاً ورعباً، وترابطه فرقة واختلافاً ونزاعاً، وهي تعتبر ظاهرة خطيرة للانتشار والفتك بالشعوب عندما تجد الأرض الخصبة لنموها وانتشارها، وخاصة مع انتشار وسائل التواصل الاجتماعي (الفيسبوك، توتير، إنستجرام) التي أسهمت بشكل كبير وملحوظ في تداول الشائعة، ومن ثم الخلل بأمن الأوطان وسلامتها، بل والأخطر من هذا هو تشويه الدين فعندما تنشر وسائل الإعلام مشاهد مرئية لبعض الغلاة وهم يقطعون الرؤوس ويحرقون الأحياء، فهذا يرسل للعالم عدداً من الرسائل السوداء والمغلوطة حتى قال بعض الأوربيين: إذا كان المسلمون على هذه القسوة مع بعضهم بعضاً فكيف ستكون قسوتهم مع مخالفيهم في الدين والمعتقد إذا حكموا وتمكنوا! فبسبب الشائعات التي تلقى عن الدين الإسلامي وأتباعه يعتقد الرجل الغربي أن الإسلام يبيح دمه بسبب الخلاف في الدين، فإن الإسلام لا يقاتل تحت بند الكفر، بل تحت بند العدوان، وتحت هذا البند لا يبالي القرآن إن كان يقاتل معتدين كفاراً أو معتدين مؤمنين. ولهذا يتوجب علينا في إطار المواجهة ضرورة العناية بدراسة الشائعة في مختلف مؤسساتنا ومعاهدنا فقد أصبحت الشائعة علماً له قوانين ونظريات ودراسات ونتائجه التجريبية والواقعية، بحيث يمكن توجيهه لتحقيق مطامع وأهداف بعينها في إطار المفهوم الشامل للحرب النفسية وللوقاية من أخطار الحرب المستمرة ضد الأوطان. ولقد قسمت الدراسة إلى تمهيد وثلاثة مباحث، على النحو الآتي: - التمهيد: حيث تم فيه عرض المصطلحات المهمة الخاصة بالدراسة كتعريف الوطن، ومصطلح الشائعات، وأسباب حدوث الشائعات، والمبحث الأول: الشائعات وأثرها في تهديد الوطن في المجتمع النبوي أما المبحث الثاني: العلاج من الشائعات في ضوء الهدي النبوي.
The circulation and spread of rumors are among the most serious political, economic, and social threats to national security, especially in important matters, and serious events such as matters of war and international relations, which, as soon as they spread in a society, its security transformed into anxiety and terror, and its interconnectedness is division, disagreement and conflict, which are It is considered a dangerous phenomenon for the spread and lethality of peoples when it finds fertile ground for its growth and spread, especially with the spread of social media (Facebook, Twitter, Instagram) that contributed significantly and significantly to the circulation of rumor, and then the defect in the safety and security of homelands, and even more dangerous than this is the distortion of religion. The media publish visual scenes of some extremists beheading and burning the living. This sends a number of black and false messages to the world so that some Europeans said: If Muslims are this cruel with each other, then how will their cruelty be with their opponents in religion and belief if they rule and are able! Because of the rumors received about the Islamic religion and its followers, the Western man believes that Islam permits his blood because of the disagreement in the religion, Islam does not fight under the clause of disbelief, but under the clause of aggression, and under this item the Qur’an does not care if he fights infidels or believing aggressors. Therefore, in the context of confrontation, we must pay attention to studying the rumors in our various institutions and institutes, as the rumor has become a science with laws, theories, studies and experimental and realistic results, so that it can be directed to achieve specific ambitions and goals within the framework of the comprehensive concept of psychological warfare and to prevent the dangers of the ongoing war against the homelands. The study was divided into an introduction and three sections, as follows: Preface: where the important terms related to the study were presented, such as the definition of the homeland, the term rumors, and the reasons for the occurrence of rumors. The first topic: rumors and their impact on the threat to the homeland in the prophetic society As for the second topic: treatment of rumors in light of the prophetic guidance.
Keywords: السيرة النبوية -- المجتمع الإسلامي -- الأمن المجتمعي -- الشائعات